Piloting Strategies in Translating Adjective - Nur Hasyim (Universitas Al Azhar Indonesia, 2021)
Parts of speech are important knowledge that needs to be known in the learning language unit to find out the appropriate meaning. Parts of speech indicate the function of the word in forming the meaning within the sentence. This research investigates the translation model of emotional intelligence terms in root word and derivative, especially in adjective type as piloting strategies in translating adjective. The research objectives are (i) to construct a translation model of translating adjectives, (ii) to describe the adjective translation model, and (iii) to describe the way to use the model. The study was using a research development approach. A model was a product of the translation stage based on translation techniques in producing good translation quality. The research was developed based on the research conducted by Nur Hasyim (2019) about “The Translation Analysis of Emotional Intelligence Terms on the book entitled Working with Emotional Intelligence by Daniel Goleman (2019)”. The substance of the model was based on proposed translation techniques such as established- equivalent, transposition, modulation, or borrowing. Those techniques are the considerable techniques that can be used to navigate in translating adjectives to obtain good translation quality.Keywords - Adjective, Emotional intelligence, Developmental research, Piloting strategies, Translation model, Translation quality.